Faktor Risiko dan Manajemen Mirror Syndrome - Muhammad Hasbi Sahbani; Nurul Islamy; Citra Yuliyanda Pardilawati; Ratna Dewi Puspita Sari (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Mirror syndrome is a rare prenatal clinical condition associated with significant fetal death and maternal morbidity. Objective: To Know more about Mirror Syndrome comprehensively. Methods: The literature review study combines the essence of several relevant sources from national and international sources. Results: Mirror syndrome is defined by the presence of a clinical trial that includes fetal hydrops, placental hydrops, and maternal oedema. Several fetoplacental diseases are also associated with MS, which can be classified into diverse groups based on: different etiologies. Conclusion: There are many things still unknown about Mirror Syndrome. Early diagnosis is essential to determine the etiology of Mirror Syndrome and the appropriate treatment according to its type.